2009
DOI: 10.1089/ars.2009.2485
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Unfolded Protein Response Regulator GRP78/BiP in Development, Cancer, and Neurological Disorders

Abstract: GRP78=BiP is a major endoplasmic reticulum (ER) chaperone protein critical for protein quality control of the ER, as well as controlling the activation of the ER-transmembrane signaling molecules. Through creation of mouse models targeting the Grp78 allele, the function of GRP78 in development and disease has been investigated. These led to the discovery that GRP78 function is obligatory for early embryonic development. However, in adult animals, GRP78 is preferably required for cancer cell survival under path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
435
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 519 publications
(447 citation statements)
references
References 78 publications
7
435
0
5
Order By: Relevance
“…In transformed cells, activation of the RAS-RAF-MEK-ERK pathway and a basal state of proteotoxic stress induces GRP78 and HDAC6 levels (33,(37)(38)(39). Increased levels of GRP78 also result from an adaptive response to proteotoxic stress and UPR and confer resistance to apoptosis (2,(4)(5)(6)(7)20). Consistent with a previous report, our findings also show that treatment with pan-HDAC inhibitor induces UPR and GRP78 levels (31).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In transformed cells, activation of the RAS-RAF-MEK-ERK pathway and a basal state of proteotoxic stress induces GRP78 and HDAC6 levels (33,(37)(38)(39). Increased levels of GRP78 also result from an adaptive response to proteotoxic stress and UPR and confer resistance to apoptosis (2,(4)(5)(6)(7)20). Consistent with a previous report, our findings also show that treatment with pan-HDAC inhibitor induces UPR and GRP78 levels (31).…”
Section: Discussionsupporting
confidence: 91%
“…GRP78 is primarily involved in the folding and assembly of newly synthesized polypeptides in the ER and chaperoning of improperly folded proteins (1,2). In a process also referred to as ER-associated degradation, GRP78 recognizes hydrophobic regions of ER-associated degradation substrates and retains them in a soluble conformation thus preventing their aggregation (1)(2)(3). ATP hydrolysis releases the misfolded proteins from GRP78, which are then retrotranslocated into the cytosol and degraded by the proteasome (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In certain types of cancer, the overexpression of BiP leads to drug resistance, recurrence, and poor patient survival. The mechanism by which BiP overexpression can contribute to cancer proliferation is linked to its ability to inactivate proapoptotic pathways and activate prosurvival pathways for cancer cells (38). Therefore, inhibition of BiP activity or downregulating of BiP expression might be useful as anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A peptide termed the 'steroidogenesis activator peptide' (SAP) was initially linked to acute stimulation of steroid synthesis (Pedersen & Brownie 1983. However, subsequent studies demonstrated that the SAP was part of the glucose-regulated protein 78 (GRP78), with no involvement in steroidogenesis (Luo et al 2006, Wang et al 2009, Wisniewska et al 2010, Wey et al 2012.…”
Section: Da Settimo Et Al (2008) Rat C6 Glioma Cellsmentioning
confidence: 99%